Ambros Rieder (1771‒1855) and the Art of Preluding - Lewandowski, Stephan (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Ambros (or Ambrosius) Mathias Rieder (1771‒1855) is perhaps one of the most underrepresented personalities of the music centre Vienna in the late 18th and first half of the 19th century in contemporary musicological and music-theoretical discourse. Both his achievements as a composer and in the field of music theory are remarkable. In particular, Rieder is to be valued and appreciated as a preserver of the tradition of prelude playing, which became increasingly less important in the late 18th and early 19th centuries. In the course of his life, he not only wrote several theoretical-practical textbooks dealing with this tradition, but with his own compositions he also provided excellent examples for the implementation of the rules presented in his theory books. With his “fugal preludes”, Rieder furthermore made a weighty contribution to the development of the genre. With the help of the music theory presented in Riederʼs Anleitung zum Präludiren auf der Orgel oder dem Piano-Forte, Op. 84, Vienna, undated [1826], this text examines the Präludien und Fughetten für die Orgel oder das Pianoforte, Op. 82, Vienna 1826 with regard to harmony, counterpoint and form-determining modulation processes. An almost striking, rarely found interlocking of theory and compositional practice is revealed. Further and more comprehensive studies on this topic are desirable.